KAJIAN KONSEP RUANG NORMA-2 DENGAN DOMAIN PEMETAAN BERUPA RUANG BERDIMENSI HINGGA - Wahidah Wahidah; Moch. Idris (EPSILON: JURNAL MATEMATIKA MURNI DAN TERAPAN, 2013)
The concept of 2-normed space was initially introduced by Gahler in 1960's.In 2001, Gunawan and Mashadi studied about 2-normed space and dene a new norm.A standard 2-normed space is an area on 2-space which is generated by two vectors.That area will be zero when the vectors are linearly dependent. In this research, we havestudied equivalency between normed space and 2-normed space.